A Comparative Study of Different Body Fat Measuring Instruments (Nigerian Journal of Physiological Sciences, 2021)
Summary: There is an increase in the occurrence of obesity worldwide. The purpose of this study was to compare various convenient and affordable body fat measuring instruments in man to percentage body fat calculated using skinfold thickness to ascertain if they can be used as a substitute for more expensive` gold standard instruments used for measuring body fat. Seventy male students (20-30years) of the University of Benin where recruited in this study. Subjects were non-athletes without systemic disease, liposuction and not on routine medication. All measurements were taken between 7am and 10am daily. Subjects came fasting refrained from exercise 12 hours before the study and body weight (kg) was measured with a digital weighing scale. A standiometer, was used to measure height (m). BMI (kg/m2) was calculated from weight and height. The Waist Circumference (WC) (cm) and Hip Circumference (HC) (m) of each subject were measured using a measuring tape. The Waist-Hip-Ratio (WHR) was calculated by dividing the subject’s WC by the HC. Skinfold thickness (mm) of the chest, abdomen and thigh were taken with a calibrated Lange skinfold caliper. Body density (BD) values were calculated using the skinfold equation of Jackson and Pollock for men. Body fat percentage (%BF) was calculated from BD using the formula of Siri, with respect to the age of each individual. Results were presented as means ± S.E.M. Microcal origin 8.0 was used to analyze collected data and correlation studies were used to investigate the relationship between groups. P values less than 0.05 were considered statistically significant. BMI, WC, HC, skinfold thickness (abdomen, thigh and Chest), weight and estimated lean body mass were positively correlated with %BF in our study population while WHR and height were weakly and negatively correlated with %BF respectively. These alternative means of assessing body fat may be useful when more sophisticated methods are unavailable.
Keywords: Percentage Body fat percentage; Obesity; Skinfold thickness; Body Mass Index